2021
DOI: 10.3390/genes12091339
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Bioinformatics Analysis Reveals Marker Genes and Potential Therapeutic Targets for Pulmonary Arterial Hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a rare cardiovascular disease with very high mortality rate. The currently available therapeutic strategies, which improve symptoms, cannot fundamentally reverse the condition. Thus, new therapeutic strategies need to be established. Our research analyzed three microarray datasets of lung tissues from human PAH samples retrieved from the Gene Expression Omnibus (GEO) database. We combined two datasets for subsequent analyses, with the batch effects removed. In the merge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Compared to previous studies, the functional modules and pathways identi ed by WGCNA method were also connected with speci c molecular subgroup of DCM [30][31][32]. We found that the speci c differential expression genes in subgroup 2 were mostly in the black, blue, green and grey WGCNA module.…”
Section: Discussionmentioning
confidence: 47%
“…Compared to previous studies, the functional modules and pathways identi ed by WGCNA method were also connected with speci c molecular subgroup of DCM [30][31][32]. We found that the speci c differential expression genes in subgroup 2 were mostly in the black, blue, green and grey WGCNA module.…”
Section: Discussionmentioning
confidence: 47%
“…Most of these studies apply machine learning methods to simulate the progression of malignancy and find significant characteristics that are then used in a categorization scheme. According to the results of our study and those of other researchers [50][51][52][53][54][55][56], this was the first study in which analytical methods for identifying PAH biomarkers use many machine learning approaches, including RF, Lasso, SVM-RFE, and WGCNA. Akter et al [57] suggest that merging different machine learning algorithms may boost prediction performance and construct highly accurate diagnostic models.…”
Section: Discussionmentioning
confidence: 64%
“…Compared to previous studies, the functional modules and pathways identified by WGCNA method were also connected with specific molecular subgroup of DCM ( Zhou et al, 2020 ; Huang et al, 2021 ; Li et al, 2021 ). We found that the specific differential expression genes in subgroup 2 were mostly in the black, blue, green and grey WGCNA module.…”
Section: Discussionmentioning
confidence: 82%